ANALYSIS OF DETERMINANTS AFFECTING THE EXPORT VOLUME OFINDONESIAN EDIBLE BIRD’S NESTS TO KEY DESTINATION COUNTRIES - I Gusti Ayu Etha Purnama Dewi; Putu Krisna Adwitya Sanjaya (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
International trade is the activity of buying and selling goods or services carried out by one country to another country in order to meet the needs in that country. The non-oil and gas export commodity in Indonesia that is currently developing, especially in the livestock sector, is the export of Indonesian swallow's nests. Problems related to the state of Indonesia's export volume tend to fluctuate, this is very important to note in order to determine the determinants that influence the increase and decrease in the volume of Indonesian swallow's nest exports to the destination country. This study aims to analyze the simultaneous and partial effects of inflation in the main destination countries for Indonesian swallow's nest exports, Gross Domestic Product in the main destination countries for Indonesian swallow's nest exports, and the USD exchange rate on the volume of Indonesian swallow's nest exports to the main destination countries. The data used is secondary data from 2012-2023 in the four main destination countries of Hong Kong, Canada, Thailand, and Singapore. The data analysis technique used in this study is panel data regression with the Fixed Effect Model (FEM) regression model. The results of the study found that inflation, GDP, and the USD exchange rate simultaneously have a significant effect on the volume of Indonesian swallow's nest exports to the main destination countries. Partially, inflation has a negative and significant effect on the volume of Indonesian swallow nest exports, while the GDP and USD exchange rates have a positive but insignificant effect on the volume of Indonesian swallow nest exports to the main destination countries. Based on the results of the study, it is expected that Indonesian swallow nest producers can produce products that suit consumer tastes in order to increase the volume of Indonesian swallow nest exports to the main destination countries.